A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini) - Benedek, Balázs; Babics, János (Zootaxa, 2017)
Panolis is a well-defined and compact Palearctic trifine Noctuidae genus within the subfamily Hadeninae, tribus Orthosiini. It is currently represented by seven species and one subspecies: Panolis flammea ([Denis & Schiffermüller], 1775), Panolis japonica Draudt, 1935, Panolis variegatoides Poole, 1989, Panolis exquisita Draudt, 1950, Panolis pinicortex Draudt, 1950, Panolis pinicortex exornata Hreblay & Ronkay, 1997, Panolis estheri Ronkay, Ronkay, Gyulai & Hacker, 2010 and Panolis ningshan Wang, Fan, Owada, Wang & Nylin, 2014. Only one species (P. flammea) occurs in the Western Palearctic region, while all others are found in the eastern part of Asia. No Panolis species is known outside of the Palearctic region. The genus is connected to coniferous woodlands as the larvae are feed on various species of pines. Imagoes are on the wing during the spring, from late February until May. All Panolis species have an unmistakable, rather decorative external appearance with fine and conspicuous pink-red-purple or dark orange ground colouration, and remarkable noctuid patterns. Most recent information about the genus was provided by Wang et. al, 2014, including his description of a new species, and a morphological and molecular analysis in order to reconstructing the phylogeny of the genus, and exploring its Chines Oriental origin. Present paper contains the description of a new Panolis species found recently in Vietnam, from where the genus was not known so far. This discovery expands our knowledge about Panolis and support the statement of the Chines Oriental origin.